2015
DOI: 10.15212/fmch.2015.0106
|View full text |Cite
|
Sign up to set email alerts
|

Menopause and the risk of metabolic syndrome among middle-aged Chinese women

Abstract: Objective: This study explored the relationship between menopause and metabolic syndrome (MetS), stroke, hyperlipidemia, diabetes and hypertension.Study design: This cross-sectional study surveyed 440 women in Yuci, China in 2012.Main outcome measures: MetS, diabetes, hypertension, hyperlipidemia, stroke, and behavioral and demographic variables.Results: The prevalence of MetS in this study was 40.28% to 49.66% (p=0.065) among preand post-menopausal women, respectively, after adjusting for age.Conclusions: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Tables 1 and 2 show the characteristics of the 44 studies included in the systematic review. The studies were from the following countries: China [21][22][23]26,27,30,[39][40][41][42][43][44][45] (n = 13), Brazil 15,16,28,[47][48][49][50] (n = 7), Iran 25,[31][32][33][34][35][36][37][38] (n = 9), India [51][52][53][54] (n = 4), Tunisia 18,20,24 FIG. 1.…”
Section: Study Characteristics and Populationsmentioning
confidence: 99%
“…Tables 1 and 2 show the characteristics of the 44 studies included in the systematic review. The studies were from the following countries: China [21][22][23]26,27,30,[39][40][41][42][43][44][45] (n = 13), Brazil 15,16,28,[47][48][49][50] (n = 7), Iran 25,[31][32][33][34][35][36][37][38] (n = 9), India [51][52][53][54] (n = 4), Tunisia 18,20,24 FIG. 1.…”
Section: Study Characteristics and Populationsmentioning
confidence: 99%
“…In a population-based study on 17 954 subjects in North-Eastern China, MetS was found to be more prevalent in men than women younger than 55 years, whereas it was higher in women than men older than 55 years 10 . Similarly, many investigators have shown that the prevalence of MetS increases with age in women—a trend not observed in men 11,13 . Sex-specific differences may be caused by testosterone and estrogen imbalances related to menopause 9 .…”
mentioning
confidence: 99%
“…10 Similarly, many investigators have shown that the prevalence of MetS increases with age in women-a trend not observed in men. 11,13 Sex-specific differences may be caused by testosterone and estrogen imbalances related to menopause. 9 Lower estrogen levels in postmenopausal women may lead to physiological changes, including visceral fat accumulation, insulin resistance, increased free fatty acid concentration, and increased hepatic lipase activity, contributing to MetS.…”
mentioning
confidence: 99%
See 2 more Smart Citations